2021
DOI: 10.1021/acsomega.1c03201
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of the Influence of Fulvic Acid from Paper Mill Effluent on Soil Properties, Soil Microbiome, and Growth of Malus hupehensis Rehd. Seedlings under Replant Conditions

Abstract: In this study, the potential regulatory effects of fulvic acid extracted from paper mill effluent (PFA) in apple replant disease (ARD) were investigated through a comprehensive experimental evaluation of the effects of PFA on soil properties, growth inhibition of apple replant pathogens, and growth of replanted Malus hupehensis Rehd. seedlings. PFA with a relatively lower molecular weight was mainly composed of carbohydrates, lignin derivatives, and polysaccharides and was rich in functional groups such as car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Fulvic acid application also increased soil N, P, and K contents. At 36 days posttransplantation, application of fulvic acid powder increased available phosphorus in soil by 185.69% compared with that of soil untreated with fulvic acid, which had better effect than the fulvic acid extracted from paper mill effluent used in a previous study (47.5 to 57.5% increase of phosphorus) ( 18 ). At 36 days posttransplantation, IBP, BP, and FA treatments increased alkali-hydrolyzable nitrogen in soil by 101.25%, 127.07%, and 90.43%, respectively.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Fulvic acid application also increased soil N, P, and K contents. At 36 days posttransplantation, application of fulvic acid powder increased available phosphorus in soil by 185.69% compared with that of soil untreated with fulvic acid, which had better effect than the fulvic acid extracted from paper mill effluent used in a previous study (47.5 to 57.5% increase of phosphorus) ( 18 ). At 36 days posttransplantation, IBP, BP, and FA treatments increased alkali-hydrolyzable nitrogen in soil by 101.25%, 127.07%, and 90.43%, respectively.…”
Section: Discussionmentioning
confidence: 77%
“…Fulvic acid could provide potassium necessary for the growth of crops. However, Wang et al ( 18 ) found that application of fulvic acid extracted from paper mill effluent had no remarkable effects on soil pH, inorganic nitrogen, available potassium, and organic matter. The effects of fulvic acid from different sources on soil nutrition varied, and the fulvic acid extracted from yeast fermentation broth had a better effect of improving soil fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Fulvic acid is a type of organic acid that plays an important role in increasing plant growth and plant drought resistance [ 161 ]. In grape berries, fulvic acid improved fruit quality and calcium absorption [ 162 ].…”
Section: Biochemical Treatments For Drought Tolerance and Their Physi...mentioning
confidence: 99%
“…Due to frequent tree species optimization, but limited land resources, it is difficult to avoid replanting cultivation in the original site during orchard renovation, which in turn leads to the widespread occurrence of ARD, and significantly restricts the sustainable development of the apple industry . Replanted young apple trees usually exhibit such phenomena as show delayed root extension, slow plant metabolism, poor resistance to stress, and even death of the whole plant . ARD causes serious economic losses throughout the whole life cycle of an orchard .…”
Section: Introductionmentioning
confidence: 99%
“… 2 Replanted young apple trees usually exhibit such phenomena as show delayed root extension, slow plant metabolism, poor resistance to stress, and even death of the whole plant. 3 ARD causes serious economic losses throughout the whole life cycle of an orchard. 4 Thus, it is urgent to develop alternative clean and green measures to control ARD.…”
Section: Introductionmentioning
confidence: 99%